HUBUNGAN PELAKSANAAN SURGICAL SAFETY CHECKLIST DENGAN KEJADIAN CEDERA (PATIENT SAFETY) DI RUMAH SAKIT MURNI TEGUH TUBAN BALI - Sejahtera, Henry Ika; Simatupang, Lenny Lusia (STIKes Mitra Husada Medan, 2024)
Surgical Safety Checklist (SSC) is a surgical team communication tool for patient safety used in the operating room. The surgical team includes the operating doctor, and nurses (instrument nurses, anesthesia nurses, circulating nurses) (Arif and Kumala, 2009). This research design uses a cross-sectional survey. Cross-sectional survey is a research design to determine the correlation with the approach and data collection at a predetermined point in time to the sample. The number of samples used in this study was 20 respondents. The Relationship between the Implementation of Surgical Safety Checklist and Injury Incidents (Patient Safety) at Murni Teguh Hospital, Tuban, Bali based on the test used, namely the Spearman Rho test, the results of the Sig value were 0.01, where the Sig value <0.05, which means that there is a significant relationship between the implementation of surgical safety checklist compliance with injury incidents during the Procedure and the correlation coefficient value obtained a result of 0.68, which means a very strong relationship.